Formulation and Characterisation of Carbamazepine Orodispersible 3D-Printed Mini-Tablets for Paediatric Use - Jiayu Hu; Rawan Fitaihi; Shorooq Abukhamees; Hend E. Abdelhakim (MDPI AG, 2023)
One of the main challenges to paediatric drug administration is swallowing difficulties, hindering the acceptability of the medicine and hence clinical outcomes. This study aims at developing a child-appropriate dosage form, the orodispersible mini-tablet (ODMT), using the model drug carbamazepine (CBZ). This dosage form was prepared and 3D-printed via a semi-solid extrusion technique. Design of Experiment methods were applied for optimising the formulation. The formulation with 40% (w/w) of SSG (superdisintegrant) and 5% (w/w) of PVP K30 (binder) was selected and loaded with CBZ. The drug-loaded tablets were characterised by a mean hardness of 18.5 N and a disintegrating time of 84 s, along with acceptable friability. The mean drug loading ratio of the tablets was tested as 90.56%, and the drug release rate in 0.1 M HCl reached 68.3% at 45 min. Excipients showed proper compatibility with the drug in physical form analysis. Taste assessment via an E-tongue was also conducted, where the drug did not show bitter taste signals at a low concentration in the taste assessment, and the sweetener also blocked bitterness signals in the testing. To this end, ODMTs were found to be potential candidates for child-appropriate dosage forms delivering CBZ.